Coastal Dynamics at Kharasavey Key Site, Kara Sea, Based on Remote Sensing Data - Georgii Kazhukalo; Anna Novikova; Natalya Shabanova; Mikhail Drugov; Stanislav Myslenkov; Pavel Shabanov; Nataliya Belova; Stanislav Ogorodov (Remote Sensing, 2023)
In recent decades, acceleration of coastal erosion has been observed at many key sites of the Arctic region. Coastal dynamics of both erosional and accretional stretches at Kharasavey, Kara Sea, was studied using multi-temporal remote sensing data covering the period from 1964 to 2022. Cross-proxy analyses of the interplay between coastal dynamics and regional (wave and thermal action) and local (geomorphic and lithological features; technogenic impact) drivers were supported by cluster analysis and wind–wave modelling via the Popov–Sovershaev method and WaveWatch III. Ice-rich permafrost bluffs and accretional sandy beaches exhibited a tendency towards persistent erosion (−1.03 m/yr and −0.42 m/yr, respectively). Shoreline progradation occurred locally near Cape Burunniy (6% of the accretional stretch) and may be due to sediment flux reversals responding to sea-ice decline. Although the mean rates of erosion were decreasing at a decadal scale, cluster analysis captured a slight increase in the retreat for 71% of the erosional stretch, which is apparently related to the forcing of wind–wave and thermal energy. Erosional hotspots (up to −7.9 m/yr) occurred mainly in the alignment of Cape Kharasavey and were predominantly caused by direct human impact. The presented study highlights the non-linear interaction of the Arctic coastal change and environmental drivers that require further upscaling of the applied models and remote sensing data.